PRELIMINARY SOMMA DATA: MITOCHONDRIAL ENERGETICS, LEG POWER, AND CARDIORESPIRATORY FITNESS. (20th December 2022) - Mau, Theresa; Coen, Paul; Kritchevsky, Stephen; Newman, Anne; Distefano, Giovanna; Hepple, Russell T; Goodpaster, Bret; Cummings, Steven
Abstract: To assess mitochondrial function, max OXPHOS (maximal complex I and II supported state 3 respiration) was determined in vitro by high-resolution respirometry of permeabilized muscle fibers from thigh muscle (vastus lateralis) biopsies, and ATPmax was determined in vivo by 31P magnetic resonance spectroscopy (n=468, mean=76.9yr). Max OXPHOS was strongly associated with leg power (β= 10.7 Watts per 1 SD increment, p<0.001) and peak VO2 (β= 83.7 mL/min, p<0.001). ATPmax had weak associations with leg power (β= 4.2 Watts per SD increment, p=0.13). In contrast to its weaker relationship with leg power, ATPmax was strongly associated with VO2 peak (β= 70.1 mL/min per SD increment, p<0.001). Skeletal muscle mitochondrial energetics were significant determinants of leg power and VO2 peak in older adults.